Latinx Gender Role Attitudes, Attachment, and Intimate Partner Violence Attitudes Among Latinx Adults Formerly Incarcerated in California - Ibarra, Xochitl; Faustino, Joselito; Banull, Cheryl; Domingo, Aldwin (Advances in Social Sciences Research Journal, 2025)
This study examined the extent to which traditional Latinx gender role attitudes (machismo and marianismo) and attachment styles (anxious and avoidant) predict intimate partner violence attitudes (IPVA) among Latinx adults formerly incarcerated in California. A cross-sectional, correlational design was employed with a sample of 119 participants who completed an online survey that included four measures, the Marianismo Beliefs Scale, Traditional Machismo and Caballerismo Scale, Experiences in Close Relationships Scale-Revised, and the Intimate Partner Violence Attitude Scale-Revised. Multiple regression analyses revealed that avoidant attachment was a significant positive predictor of IPVA, while anxious attachment was a marginally significant predictor. Traditional Latinx gender role attitudes, specifically beliefs about women’s subordination and self-silencing, emerged as strong IPVA predictors, while other Latinx gender role attitude dimensions were not significant. The hierarchical regression model demonstrated that the combined predictors explained 41.6% of the variance in IPVA, with traditional Latinx gender role attitudes exerting a stronger influence than attachment styles. Findings highlighted the role of cultural and relational dynamics in shaping IPVA and emphasized the need for culturally tailored prevention and early IPV interventions.